PENGARUH MARKETING PUBLIC RELATION DAN BRAND IMAGE TERHADAP LOYALITAS PELANGGAN (Studi Pada PT. JNE Cabang Samosir) - Girsang, Herinto; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at PT. JNE Cabang Samosir, as for the purpose of this study was to determine the effect of marketing public relation and brand image to costumer loyalty ( study at PT. JNE Cabang Samosir). marketing public relation and brand image as the independent variable (X1X2) while the costumer loyalty as the dependent variable (Y). The problem in this research is the sale of room service of PT. JNE Cabang Samosir experinced fluctuated every year, does not even reach the sales target. Seen from the presentation realization of sale in the company in the last 5 years. The research sample was taken of 100 respondents of the population was calculated using the Slovin formula. The data was getting from the questionnaire and subsequently processed to then be tested with statistics through SPSS. From the results which shows that marketing public relation and brand image has a positive and significant impact on customer loyalty (study at PT. JNE Cabang Samosir)Keywords: marketing public relation, brand image and customer loyalty